Methylation status of promoter 1 region of GDNF gene in human glioma cells - Chen, Maohua (e-Century Publishing Corporation, 2014)
Objective: This study aimed to investigate the methylation status of promoter 1 region of glial cell line-derived neurotrophic factor (GDNF) in human glioma cells and to explore the effect of GDNF methylation on the expression of GDNF in glioma. Methods: GDNF gene mutation was detected by sequencing in 10 patients with glioma and 5 healthy controls. Bisulfite modification for analysis of DNA methylation was done to detect the methylation status of promoter 1 region of GDNF in 20 patients with glioma (10 with poorly differentiated and 10 with well differentiated) and 5 healthy controls. Results: There was no mutation at the promoter 1 region of GDNF gene in glioma. The incidence of methylation of GDNF gene at the promoter 1 region in healthy control, patients with poorly differentiated glioma and those with well differentiated glioma was 72.25%, 86.25% and 86.75%. The incidence of GDNF methylation in glioma was significantly higher than that in the normal brain (P<0.05); while there was no significant difference between well differentiated glioma and poorly differentiated glioma. Conclusions: Hypermethylation occurs in the promoter 1 region of GDNF and may influence the expression of GDNF in glioma.